1991
DOI: 10.1111/j.1651-2227.1991.tb11783.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Respiratory Physiological Effects of a Physical Exercise Programme on Boys with Severe Asthma

Abstract: Psychological and respiratory physiological effects of a physical exercise programme on boys with severe asthma. Acta Paediatr Scand 80: 1058, 1991. Ten boys 9-12 years of age with severe perennial asthma participated in a physical exercise programme lasting 8 months. Pulmonary function and psychological tests were performed before training, immediately after, and one year after the end of the exercise programme. Static lung volumes, flow-volume variables and histamine tolerance were used as indicators of pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Thus, Strunk et al [25] showed that the wide variability in aerobic performance in a group of 90 children with moderate and severe asthma was mainly related to the degree of social and disease adjustment. Engström et al [26] in a group of 10 severely asthmatic children submitted to physical training showed that only psychological modifications correlated significantly with aerobic improvement. Thus, individual variations in acceptance and knowledge of the disease seem to influence the usual level of physical activity in asthmatic children, and therefore their degree of fitness.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, Strunk et al [25] showed that the wide variability in aerobic performance in a group of 90 children with moderate and severe asthma was mainly related to the degree of social and disease adjustment. Engström et al [26] in a group of 10 severely asthmatic children submitted to physical training showed that only psychological modifications correlated significantly with aerobic improvement. Thus, individual variations in acceptance and knowledge of the disease seem to influence the usual level of physical activity in asthmatic children, and therefore their degree of fitness.…”
Section: Discussionmentioning
confidence: 98%
“…However, we did not find a significant reduction in the prevalence of a positive EIB test with training, regardless of whether or not there was a positive response (Figure 2). Another more plausible hypothesis is that the improvement was related to a higher degree of acceptance and level of self-care in the least fit patients who usually have negative attitudes toward their disease and exertion [25,26]. Thus, Strunk et al [25] showed that the wide variability in aerobic performance in a group of 90 children with moderate and severe asthma was mainly related to the degree of social and disease adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…This gradual change of concept represent a big advance against old paradigms, and is based in a growing number of clinical and experimental studies showing that the regular practice of aerobic exercises in appropriate volume and intensity results in several physical and psychological beneficial effects to asthmatic patients [5][6][7][8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…increase in ventilatory capacity) and asthmarelated symptoms "asthma-control" (e.g. dyspnea, exercise-induced bronchospasm or peak expiratory flow variability) [5][6][7][8][9][10][11][12][13][14][15]. In addition a decrease of daily use of inhaled steroids has been reported, suggesting an anti-inflammatory effect of exercise on asthmatic lungs [5][6][7][8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
See 1 more Smart Citation